The Effect of Foliar Selenium (Se) Treatment on Growth, Photosynthesis, and Oxidative-Nitrosative Signalling of Stevia rebaudiana Leaves - Péter Borbély; Árpád Molnár; Emil Valyon; Attila Ördög; Klára Horváth-Boros; Dezső Csupor; Attila Fehér; Zsuzsanna Kolbert (MDPI AG, 2021)
Selenium (Se) enrichment of Stevia rebaudiana Bertoni can serve a dual purpose, on the one hand to increase plant biomass and stress tolerance and on the other hand to produce Se fortified plant-based food. Foliar Se spraying (0, 6, 8, 10 mg/L selenate, 14 days) of Stevia plantlets resulted in slightly decreased stevioside and rebaudioside A concentrations, and it also caused significant increment in stem elongation, leaf number, and Se content, suggesting that foliar Se supplementation can be used as a biofortifying approach. Furthermore, Se slightly limited photosynthetic CO2 assimilation (AN, gsw, Ci/Ca), but exerted no significant effect on chlorophyll, carotenoid contents and on parameters associated with photosystem II (PSII) activity (FV/FM, F0, Y(NO)), indicating that Se causes no photodamage in PSII. Further results indicate that Se is able to activate PSI-cyclic electron flow independent protection mechanisms of the photosynthetic apparatus of Stevia plants. The applied Se activated superoxide dismutase (SOD) isoenzymes (MnSOD1, FeSOD1, FeSOD2, Cu/ZnSOD1, Cu/ZnSOD2) and down-regulated NADPH oxidase suggesting the Se-induced limitation of superoxide anion levels and consequent oxidative signalling in Stevia leaves. Additionally, the decrease in S-nitrosoglutathione reductase protein abundance and the intensification of protein tyrosine nitration indicate Se-triggered nitrosative signalling. Collectively, these results suggest that Se supplementation alters Stevia shoot morphology without significantly affecting biomass yield and photosynthesis, but increasing Se content and performing antioxidant effects, which indicates that foliar application of Se may be a promising method in Stevia cultivation.